Implementation of Space Vector Modulation for Voltage Source Inverter - Sanusi, Syamim; Ibrahim, Zulkifli; Jidin , Auzani; JOPRI, MOHD HATTA; Abdul Karim, Kasrul; Othman, Md Nazri (2013)
This paper presents a development of a voltage source inverter (VSI) for electrical drive applications based on Space Vector Modulation (SVM) technique and the SVM algorithm is implemented using digital signal processor (DSP). Space Vector Modulation has become a popular technique to control an induction machine by referring to a special switching sequence which is based on the upper switches of a 3 phase voltage source inverter (VSI). As a result, SVM technique provides better performance characteristic in comparison to sinusoidal pulse width modulation (SPWM) in term of higher dc bus utilization and better total harmonic distortion (THD). A simple method to produce space vector modulation using an algorithm that easy to implement to DSP are develop in this paper. The developed techniques are verified via simulation and experiment to analyze the harmonic performance.